Filteration of Morality Values in Book “Islam yang Mencerahkan dan Mencerdaskan” by K.H. Husein Muhammad - Fatul, Fitasari; Ichsan, Ahmad Shofiyuddin; Kuswanto, Heri (Pusat Studi Penelitian dan Evaluasi Pembelajaran, 2024)
This research aimed to determine the filtering of moral values in the book Islam that Enlightens and Intelligents (Islam yang Mencerahkan dan Mencerdaskan) by KH. Husein Muhammad and revealed the relevance of the moral values in this book in the contemporary era. Researchers used a literature review in this research with sources from various relevant documentation. The results of the study showed that the filtering of moral values in the book Islam yang Mencerahkan dan Mencerdaskan included several things, namely 1) being aware of good and bad deeds, 2) the ability to do good things, 3) knowing the condition of one's morality. The relevances of this book in the current era were 1) a person needs to prioritize the purity of his soul, 2) be willing to go abroad in search of knowledge, and 3) not be arrogant about knowledge and oppose teachers.